Case Based Reasioning (CBR) for Medical Question Answering System - Setio Basuki; Alfira Rizky; Galih Wasis Wicaksono (Universitas Muhammadiyah Malang, 2018)
In this research, the researchers implement a medical Question Answering System (QAS), a complaint system in the form of sentences or paragraphs of questions about the complaint (illness) suffered by a person. Afterwards, the system will give answer to the questions with answers in the form of diagnosis based on the system knowledge. The system in this study has knowledge of the system obtained based on Case Based Reasoning (CBR) method from the previous cases stored in the database. When there is a new case, the system will perform a matching process using CBR and Sorenson Coefficient calculations to find out which the previous cases have the highest percentage of matches with the new case. Then the selected previous cases will be taken and given to the new case. Testing is processed by using 2 types of testing, expert validation testing with result of 28 data of appropriate test from 30 test data and accuracy testing resulting of 93,33% from the appropriate test data.